Forest inventory information needs in Northwest Russia - Höök, Veronika (2015)
This thesis applies the customer value hierarchy model to forestry in order to determine strategic options to enhance the value of LiDAR technology in Russian forestry. The study is conducted as a qualitative case study with semi-structured interviews as a main source of the primary data. The customer value hierarchy model constitutes a theoretical base for the research. Secondary data incorporates information on forest resource management, LiDAR technology and Russian forestry. The model is operationalised using forestry literature and forms a basis for analyses of primary data. Analyses of primary data coupled with comprehension of Russian forest inventory system and knowledge on global forest inventory have led to conclusions on the forest inventory methods selection criteria and the organizations that would benefit the most from LiDAR technology use. The thesis recommends strategic options for LiDAR technology’s value enhancement in Russian forestry. Tässä diplomityössä sovelletaan asiakkaan kokeman arvon hierarkian mallia metsätalouteen. Mallia sovelletaan LiDAR teknologian strategisten vaihtoehtojen määrittämiseen Venäjän metsäinventoinnissa. Diplomityö on laadullinen tapaustutkimus, jossa puolistrukturoituja haastatteluja käytettiin aineistonhankintamenetelmänä. Asiakkaan kokeman arvon hierarkian malli muodostaa tutkimuksen teoreettisen perustan. Sekundaariaineisto koostuu metsävarojen hallintaan, LiDAR teknologiaan sekä Venäjän metsätalouteen liittyvästä aineistosta. Asiakkaan kokeman arvon hierarkian malli on operationalisoitu käyttäen metsätiedon kirjallisuutta ja toimii primaariaineiston analyysin perustana. Primaariaineiston analyysi yhdessä Venäjän metsäinventoinnin järjestelmän ja maailmanlaajuisen metsäinventoinnin tiedon kanssa oli johtanut diplomityön tuloksiin. Tutkimuksessa oli määritelty Venäjän metsätiedon käyttäjät, jotka hyötyvät eniten LiDAR teknologian käytöstä sekä oli määritelty metsäinventointiteknologien arvosteluperusteet. Diplomityössä esitetään strategiset vaihtoehdot LiDAR ...